Exploring the impact of work-related potential traumatic events among Dutch psychiatrists. (June 2020) - Scheepstra, K.W.F.; van Lent, E.M.; Lok, A.; Olff, M.; van Pampus, M.G.
Highlights: This survey implies that psychiatrists frequently experience work-related PTEs (78.4%), often with a significant emotional impact. Verbal aggression, physical violence or completed suicide are the most common work-related PTEs. Most reported posttraumatic stress (PTS) symptoms were hyperarousal, sleeping difficulties and intrusive thoughts. The majority of Dutch (resident) psychiatrists learned coping styles while working as a physician, intervision groups (e.g. Balint) and/or learning therapy. Abstract: Psychiatrists are frequently exposed to work-related potential traumatic events (PTEs). A survey was sent to the members of the Dutch Society of Psychiatrists of which 250 questionnaires were eligible for analysis. At least one work-related PTE was reported by 196 (78.4%) of the respondents, of which 177 described the PTE. Witnessing or experiencing verbal aggression (29.2%), physical violence (29.2%) or completed suicide (26.8%) were the most common PTEs. This survey implies that psychiatrists frequently experience work-related PTEs, often with a significant emotional impact. The majority of respondents considered current support as insufficient.